The chemical basis of a signal of individual identity: shell pigment concentrations track the unique appearance of Common Murre eggs. Issue 153 (26th April 2019) - Hauber, Mark E.; Bond, Alexander L.; Kouwenberg, Amy-Lee; Robertson, Gregory J.; Hansen, Erpur S.; Holford, Mande; Dainson, Miri; Luro, Alec; Dale, James
Abstract : In group-living species with parental care, the accurate recognition of one's own young is critical to fitness. Because discriminating offspring within a large colonial group may be challenging, progeny of colonial breeders often display familial or individual identity signals to elicit and receive parental provisions from their own parents. For instance, the common murre (or common guillemot: Uria aalge ) is a colonially breeding seabird that does not build a nest and lays and incubates an egg with an individually unique appearance. How the shell's physical and chemical properties generate this individual variability in coloration and maculation has not been studied in detail. Here, we quantified two characteristics of the avian-visible appearance of murre eggshells collected from the wild: background coloration spectra and maculation density. As predicted by the individual identity hypothesis, there was no statistical relationship between avian-perceivable shell background coloration and maculation density within the same eggs. In turn, variation in both sets of traits was statistically related to some of their physico-chemical properties, including shell thickness and concentrations of the eggshell pigments biliverdin and protoporphyrin IX. These results illustrate how individually unique eggshell appearances, suitable for identity signalling, can be generated by a small number of structural mechanisms.